The approximation of bivariate functions by modified bivariate operators and GBS operators associated - Pop, Ovidiu T. (Rev. Anal. Numér. Théor. Approx., 2012)
In this paper we demonstrate a Voronovskaja-type theorem and approximation theorem for a class of modified operators and Generalized Boolean Sum (GBS) associated operators obtained (see (3)) from given operators.